Hubungan Supervisi Akademik Kepala Sekolah Dan Pengawasan Guru Dalam Mengajar Dengan Kompetensi Profesional Guru SD Negeri 15 Tumbang Titi - Oktavia Fransiska; Herry Sanoto (Departement of Mathematics Education, 2023)
The principal has the obligation to manage the running of the school and can also collaborate and relate closely with the community, raising the enthusiasm of the staff of teachers and school employees to work better. The function of monitoring or supervision in education is not just control to see whether all activities have been carried out in accordance with the plans and programs that have been outlined, but more than that. A school principal has the authority to develop and improve teacher supervision in teaching with professional competence. This research aims to determine the relationship between principals' academic supervision and teacher supervision in teaching with the professional competence of teachers in elementary schools. This can be seen from the calculations in the description above, it can be seen that the sig (2-tailed) value of variable X for variables Y1 and Y2 is 0.408 and 0.171. Where these two values ​​have exceeded the 5% (0.05) significance level that has been set, so it can be concluded that there is a significant relationship between the academic supervision variable (X) and the teacher supervision variable in teaching (Y1) and teacher professionalism (Y2). . From the explanation above, it is stated that there is a positive and significant relationship between academic supervision, teacher supervision in teaching and teacher professionalism at SD Negri 15 Tumbang Titi.